Repair technology of crack defects in revetment under surge and impact loads
Through the process of combining magnetic concrete and magnetic anchor rods, magnetic field oscillation and fiber web adsorption, the complexity and durability of traditional concrete in the repair of bank revet under surge and impact loads is solved, and efficient and rapid crack filling and Improved shear resistance.
Patent Information
- Application Number
- CN202211241532.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-11
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-10-11
AI Technical Summary
Traditional concrete is prone to cracks under surge and impact loads. The repair process is complex and has poor effect, insufficient shear resistance, and poor durability, making it difficult to effectively repair shore protection cracks in marine environments.
The process of combining magnetic concrete and magnetic anchor rods is adopted to realize real-time regulation and full filling of magnetic concrete through magnetic field oscillation and fiber web adsorption, improve shear resistance, overcome gravity, and adapt to the underwater construction environment.
The construction process is simplified, the shear resistance and durability of magnetic concrete is improved, and it can quickly condense and fully fill cracks, reducing construction costs and time, and significantly improving the repair effect.
Smart Images

Figure CN115749342B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of crack repair, and in particular to a process for repairing crack defects in bank protection under surge and impact loads. Background Art
[0002] Traditional concrete has its own shortcomings. Under load and extreme weather conditions, concrete in some buildings will expand and contract. Due to uneven settlement of the foundation and some factors such as construction process quality, cracks will occur. Traditional solutions for repairing cracks include surface repair and local repair, which are complex and time-consuming. New cracks may appear after a certain period of time. Concrete viscosity cannot be adjusted in real time and has poor durability. Concrete is easily washed away. Concrete water cannot be fully removed. Concrete has poor shear resistance and is easy to segregate.
[0003] Surge is a common phenomenon of ocean dynamics. Surge will generate impact load. When the surge propagates from the deep water area to the shallow water area, it will be affected by the change of regional terrain, causing shallowing and breaking of the revetment. These phenomena are the focus of ocean dynamics research. The marine topography is different from the common slowly changing terrain. The water depth changes dramatically and the surge has a strong nonlinear change characteristic when interacting with it. It causes great damage to the revetment under surge and impact load. Traditional concrete material repair, under the action of surge and impact load, the concrete loss is serious, the construction period is extended, the cost is increased, the concrete construction process is complicated, the effect is not good, the concrete of small cracks is not easy to inject, and it is difficult to seal. Concrete has the disadvantages of insufficient shear resistance and easy segregation. New cracks may appear after a certain period of time. The viscosity of concrete cannot be controlled in real time and the durability is poor. The concrete is easily washed away and the concrete water cannot be fully removed.
[0004] CN113250483A discloses a device and method for repairing building cracks by pre-embedded and prefabricated magnetic attraction end-guided method based on magnetic force, which improves the crack filling effect of the building through magnetic concrete. However, the current prior art has not yet disclosed a magnetic concrete repair process under impact load. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a repair process for crack defects in bank protection under surge and impact loads, so that magnetic concrete can be gathered at the crack defect position, the shear resistance of magnetic concrete can be improved, and all gaps can be fully filled.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a process for repairing crack defects of revetment under surge and impact loads, comprising the following steps:
[0007] Step 1: preparing magnetic concrete;
[0008] Step 2: Detect the width, depth, length and location of the crack, and perform surface debridement;
[0009] Step 3: Place a fiber mesh at the hole of the crack. The fiber mesh is magnetic. The end of the magnetic anchor absorbs the magnetic concrete. The fiber mesh is pushed into the hole of the crack through the magnetic anchor so that the fiber mesh fits the inner wall of the hole of the crack.
[0010] Step 4: Place the concrete pouring conduit on one side of the magnetic anchor rod and inject magnetic concrete. At the same time, the magnetic anchor rod adjusts its magnetic strength to cause magnetic field oscillation.
[0011] In a preferred solution, in step 1, the magnetic concrete preparation operation is as follows:
[0012] S1. Put cement and water reducing agent into a container and stir them to mix them evenly, then add water to make cement and water produce hydration reaction;
[0013] S2. Add epoxy resin to the container containing magnetic powder and stir to mix, then add flocculant and iron sand and stir thoroughly;
[0014] S3. Mix the slurry prepared in S1 with the slurry prepared in S2, and then add aggregate and stir.
[0015] In a preferred embodiment, in S1, the mass proportion of the water reducing agent is 0.5%.
[0016] In a preferred embodiment, in S2, the mass ratio of magnetic powder, epoxy resin, flocculant and iron sand is 2:1:1:6.
[0017] In a preferred embodiment, in S3, the ratio of the slurry prepared in S1 to the slurry prepared in S2 is 1:2.
[0018] In a preferred solution, in S3, the material of the aggregate is ceramsite, foam, waste concrete, iron ore, or slag crushed stone.
[0019] In a preferred solution, in step three, the magnetic anchor rod comprises a hollow anchor rod, and an electromagnet is provided in the hollow cavity of the hollow anchor rod.
[0020] The present invention provides a process for repairing crack defects in bank protection under surge and impact loads, which has the following beneficial effects:
[0021] 1. The traditional construction method requires formwork, steel bar tying, and then pouring concrete, which requires a lot of material and labor costs. In addition, the concrete is easily washed away during underwater construction, and the density and fluidity of the concrete cannot be guaranteed, and the shear resistance of the concrete is insufficient. A magnetic concrete preparation method does not require a large number of formworks and steel bars, and the construction process becomes simple. By adjusting the proportion of magnetic concrete and the size of the magnetic field, the viscosity of the magnetic concrete can be adjusted in real time. It is resistant to dispersion, erosion, and rapid coagulation in a water environment, and has a large shear resistance.
[0022] 2. The magnetic anchor rod absorbs the end of the magnetic concrete, adjusts its magnetic strength, causes magnetic field oscillation, completes the drainage and exhaust of its pouring process, and achieves a dense effect. While pouring magnetic concrete, the strength of the magnetic field can be controlled, so that the magnetic concrete gathers at the magnetic concrete injection port, improves the shear resistance of the magnetic concrete, reduces the magnetic field strength, increases the fluidity of the magnetic concrete, and fully fills all pores. By setting a magnetic fiber mesh to absorb the magnetic concrete, the magnetic concrete can be fully filled in the hole.
[0023] 3. Magnetic concrete can be filled in an anti-gravity manner. By adjusting the proportion of magnetic concrete, increasing the content of magnetic materials, and enhancing the magnetic adsorption effect, the gravity of the magnetic concrete itself can be overcome to achieve anti-gravity magnetic concrete, which can resist high water head in underwater construction environments.
[0024] 4. Place the electromagnet inside the hollow anchor rod, the electromagnet is located at the center of the hollow anchor rod, and by adjusting the size of the electromagnet magnetic field, gradually increase the current magnetic field strength, inject magnetic concrete into the casting conduit, and under the action of the magnetic field, gather around the hollow anchor rod. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The present invention will be further described below in conjunction with the accompanying drawings and implementation examples:
[0026] Figure 1 It is a schematic diagram of the structure of the magnetic anchor;
[0027] Figure 2 This is the process diagram for repairing crack defects in bank protection;
[0028] Figure 3 This is a schematic diagram of the magnetic anchor's magnetic field affecting the induction line;
[0029] Figure 4 It is the variation trend diagram of adsorption diameter under different magnetic field strengths;
[0030] Figure 5 It is a schematic diagram of the diameter structure of adsorbed magnetic concrete;
[0031] Figure 6 Schematic diagram of the self-aggregation ability of magnetic self-aggregation slurry;
[0032] Figure 7 This is a comparison chart of the filling area between magnetic self-polymerizing slurry and ordinary slurry;
[0033] Figure 8 The graph showing the changes in the gap area and the number of gaps corresponding to different magnetic field intensities;
[0034] In the figure: electromagnet 1, hollow anchor rod 2, fiber mesh 3, hole 4, casting conduit 5, magnetic concrete 6, magnetic induction line 7, magnetic anchor rod 8, effective magnetization area 9, unmagnetized area 10. DETAILED DESCRIPTION
[0035] Embodiment 1: A process for repairing crack defects of bank protection under surge and impact loads, comprising the following steps:
[0036] Step 1: Prepare magnetic concrete. The preparation operation is as follows:
[0037] S1. Put cement and water reducer into the container and stir them. The weight of water reducer accounts for 0.5%. Use naphthalene-based high-efficiency water reducer. Stir quickly to mix the two evenly, and then add water to make cement and water produce hydration reaction. Water reducer is beneficial to improve the fluidity of magnetic concrete, make the structure more stable, and increase the strength. At the same time, it can save cement without changing the strength of magnetic concrete.
[0038] S2. Add epoxy resin to a container containing magnetic powder and stir to mix. Oily epoxy resin can be used for underwater crack repair, and water-based epoxy resin can be used for road crack repair. Epoxy resin magnetic concrete can fill cracks with a large area under the induction of magnetic force.
[0039] The epoxy resin and magnetic powder are mixed so that the magnetic powder is fully wrapped by the epoxy resin, which reduces the contact between the magnetic powder and the outside world and enhances the durability of the magnetic concrete. The magnetic particles must be evenly suspended in the magnetic concrete to achieve controllable flow of the magnetic concrete under the action of magnetic force, so as to prevent the magnetic particles from being precipitated under the induction of magnetic force.
[0040] Then add flocculant and iron sand and stir thoroughly. The mass ratio of magnetic powder, epoxy resin, flocculant and iron sand is 2:1:1:6.
[0041] S3, mix the slurry prepared in S1 with the slurry prepared in S2, fully mix the two slurries together, and quickly stir and vibrate to increase the fluidity of the mixed slurry, discharge the air and excess water in the mixed magnetic concrete, which is beneficial to reduce the porosity of the magnetic concrete and prevent the formation of honeycomb holes. Then add aggregate and stir, the ratio of the slurry prepared in S1 to the slurry prepared in S2 is 1:2.
[0042] The material of aggregate is ceramsite, foam, waste concrete, iron ore or slag crushed stone.
[0043] When foam is used as aggregate, it is very light and can generate a strong magnetic force under the action of the magnetic field. It does not need to overcome its own weight and can drive the surrounding magnetic concrete to move together. Iron ore, broken iron blocks, and iron slag are used as aggregates. Magnetic concrete can be magnetized so that the aggregates are tightly adsorbed around the hollow anchor rods and are not easy to lose under the action of wave loads. As coarse aggregate, ceramsite can increase the fluidity of magnetic concrete with a larger roundness, making the density of magnetic concrete better. Slag crushed stone is used as aggregate. Magnetic concrete has good corrosion resistance and the aggregate is easy to obtain and cheap.
[0044] The shape of the aggregate design can be designed to be circular, polygonal, concave polygonal, etc. The larger the specific surface area of the aggregate, the more magnetic concrete slurry can be adsorbed on the surface, and under the action of the magnetic field, the magnetic concrete moves in a directional manner.
[0045] Step 2: Detect the crack width, depth, length and location, and perform surface debridement.
[0046] Step 3: Figure 2 As shown, a fiber mesh is placed in the hole of the crack. The fiber mesh has magnetism. The end of the magnetic anchor absorbs the magnetic concrete and gathers around the magnetic anchor under the action of the magnetic field. The diameter of the magnetic anchor is d B , the diameter of the adsorbed magnetic concrete is d, and the height is h, such as Figure 5 shown.
[0047] The fiber mesh is pushed into the hole of the crack by means of magnetic anchor rods, and other anchor rods are placed into the hole at a certain interval. The interval distance is determined according to the magnetic influence range of the magnetic anchor rods. The fiber mesh is pushed into the hole to make it fit well with the hole wall.
[0048] Preferably, Figure 1 As shown, the magnetic anchor includes a hollow anchor, and an electromagnet is arranged in the hollow cavity of the hollow anchor, and the electromagnet is connected to a controllable switch through a wire. By setting the electromagnet, the magnetic force between the magnetic concrete and the hollow anchor can be adjusted. While pouring the fixed end of the magnetic concrete, the oscillation frequency or amplitude of the magnetic field at the magnetic attraction end can be used to complete the drainage and exhaust of the pouring process, thereby achieving a dense effect. The viscosity of the magnetic concrete can be adjusted in real time to increase the shear strength of the magnetic concrete.
[0049] Step 4: Place the concrete pouring conduit on one side of the magnetic anchor rod, inject magnetic concrete, adjust the magnetic strength of the magnetic anchor rod, cause magnetic field oscillation, and let the fiber mesh absorb the magnetic concrete to fill the pores in the hole wall, ensuring that the magnetic concrete fills the hole.
[0050] like Figure 3 and Figure 6As shown, the magnetic anchor absorbs the end of the magnetic concrete, adjusts its magnetic strength, causes magnetic field oscillation, completes the drainage and exhaust of its pouring process, and achieves a dense effect. While pouring magnetic concrete, the strength of the magnetic field can be controlled, so that the magnetic concrete gathers at the magnetic concrete pouring port, improves the shear resistance of the magnetic concrete, reduces the magnetic field strength, increases the fluidity of the magnetic concrete, and fully fills all pores.
[0051] Magnetic concrete can be filled in an anti-gravity manner. By adjusting the proportion of magnetic concrete, increasing the content of magnetic materials, and enhancing the magnetic adsorption effect, the gravity of the magnetic concrete itself can be overcome to achieve anti-gravity magnetic concrete, which can resist high water head in underwater construction environments.
[0052] The test was conducted under the ratio of 30% magnetic powder in the oily epoxy resin test. The diameter d of the adsorbed magnetic concrete under different magnetic field strengths was measured. The change trend of the diameter is as follows: Figure 4 When the magnetic powder content is the same, the adsorption self-aggregation diameter gradually increases with the increase of magnetic field intensity.
[0053] The concrete structure is 30cm long and 20cm wide. The filling area of magnetic self-polymerizing slurry and ordinary slurry is calculated by using the image seepage area digital self-identification technology, such as Figure 7 As shown, the filling area of the magnetic self-polymerizing slurry is 549.12 cm 2 , the filling area of ordinary slurry is 232.98cm 2 The filling rate can be calculated based on the slurry filling area. The calculation shows that the local filling rate of magnetic self-polymerizing slurry is 91.5%, and the local filling rate of ordinary slurry is 38.8%. The lateral filling rate of magnetic self-polymerizing slurry is more than doubled compared with ordinary slurry.
[0054] When the magnetic field intensity increases from 400GS to 6000GS, the pore area decreases by 77.6% and the pore number decreases by 76.8%. Figure 8 shown.
[0055] Example 2: The difference from Example 1 is that in step 2, for large-scale defects, self-flowing magnetic concrete is first used to fill them, and then secondary inspection and repair are carried out for defects that cannot be completed by self-flowing magnetic concrete. According to the number of embeddings in the repair plan, a corresponding number of embedding holes are drilled at specific positions in the cavity, and then the subsequent steps three to four are performed on the embedding holes.
[0056] Embodiment 3: The difference from Embodiment 1 is that different repair methods are used for cavities with different erosion depths on the revetment structure. In areas with smaller slopes, self-flowing magnetic concrete is first used for filling; in areas with larger slopes, the free section extending out of the slope is covered with a film bag, and blocks are placed in the mold bag. The treated fixed end of the injected magnetic concrete is arranged in the embedding hole, and magnetic concrete is injected into the mold bag for embedding. After the strength is generated, a certain number of test blocks are taken out from the fixed end of the injected magnetic concrete for preliminary filling of the cavity to reduce the cost of using magnetic concrete. After the preliminary filling is completed, the cavity is operated in subsequent steps three to four, so that the magnetic concrete fully fills the cracks of the test blocks and other tiny cavities that have not been filled.
[0057] Example 4: For larger amounts of erosion damage, depending on the location and shape of the damage, one or more materials such as blocks of stone, bagged sand filled with a certain amount of cement slurry, prefabricated mold bag concrete, etc. can be used for initial filling, and a cover net can be used to cover the initial filling. The magnetic concrete fixed end embedding technology is used to position and cast the cover net. Finally, the subsequent steps three to four are performed at appropriate locations around to fill the gaps between the initial fillings and improve the integrity of the embedded body and the repair object.
Claims
1. A process for repairing crack defects of revetment under surge and impact loads, characterized in that: The steps include: Step 1: preparing magnetic concrete; Step 2: Detect the width, depth, length and location of the crack, and perform surface debridement; Step 3: placing a fiber mesh at the hole of the crack, the fiber mesh is magnetic, the end of the magnetic anchor rod absorbs the magnetic concrete, and the fiber mesh is pushed into the hole of the crack through the magnetic anchor rod, so that the fiber mesh fits with the inner wall of the hole of the crack; the magnetic anchor rod includes a hollow anchor rod, and an electromagnet is arranged in the hollow cavity of the hollow anchor rod; Step 4: Place the concrete pouring conduit on one side of the magnetic anchor rod and inject magnetic concrete. At the same time, the magnetic anchor rod adjusts its magnetic strength to cause magnetic field oscillation.
2. The process for repairing crack defects of bank protection under surge and impact loads according to claim 1 is characterized in that: In the step 1, the magnetic concrete preparation operation is as follows: S1. Put cement and water reducing agent into a container and stir them to mix them evenly, then add water to make cement and water produce hydration reaction; S2. Add epoxy resin to the container containing magnetic powder and stir to mix, then add flocculant and iron sand and stir thoroughly; S3. Mix the slurry prepared in S1 with the slurry prepared in S2, and then add aggregate and stir.
3. The process for repairing crack defects of revetment under surge and impact loads according to claim 2 is characterized in that: In the S1, the mass proportion of the water reducing agent is 0.5%.
4. The process for repairing crack defects of revetment under surge and impact loads according to claim 2 is characterized in that: In S2, the mass ratio of magnetic powder, epoxy resin, flocculant and iron sand is 2:1:1:
6.
5. The process for repairing crack defects of revetment under surge and impact loads according to claim 2 is characterized in that: In S3, the ratio of the slurry prepared in S1 to the slurry prepared in S2 is 1:
2.
6. The process for repairing crack defects of bank protection under surge and impact loads according to claim 2 is characterized in that: In S3, the material of the aggregate is ceramsite, foam, waste concrete, iron ore or slag crushed stone.
Citation Information
Patent Citations
Pre-embedded and prefabricated magnetic attraction end guiding type building crack repairing device and method based on magnetic force
CN113250483A
Construction method of magnetic mortar anchoring body
CN110042834A
Underwater crack repairing method for coral sand hydraulic reclamation island reef revetment slope
CN111749241A
